PLURIMETODOLOGI KONSEP PRA-ADAM DITINJAU DARI PERSPEKTIF PAUL FEYERABEND - , RIZKIA AULIA RAMADANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The plural-methodology of preadamite concept as Paul Feyerabend viewed gives knowledge about many kinds of methodology that discusses the preadamite concept. Methodology is one of the main elements in a research and one of the main concerns for Feyerabend as he wrote it in Against Method. Feyerabend concern was against the fact that only one methodology is valid for a research. There are three problems of the research that are, first the explanation about the methodologies that discusses the preadamite concept. Second is the frame of mind of Feyerabend in his book, Against Method. The last problem is the methodology analysis about preadamite concept from Feyerabend point of view. The method of this research is literature review to understand the methodologies that discusses the preadamite concept. The sources of Feyerabendâs frame of mind are taken from the primary data which is his own book, Against Method. The methodological steps are description, interpretation and heuristics. There are three main results of this research